1998
DOI: 10.1046/j.1365-294x.1998.00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Empirical evaluation of preservation methods for faecal DNA

Abstract: We evaluate the relative effectiveness of four methods for preserving faecal samples for DNA analysis. PCR assays of fresh faecal samples collected from free-ranging baboons showed that amplification success was dependent on preservation method, PCR-product size, and whether nuclear or mitochondrial DNA was assayed. Storage in a DMSO/EDTA/Tris/salt solution (DETs) was most effective for preserving nuclear DNA, but storage in 70% ethanol, freezing at -20 degrees C and drying performed approximately equally well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
209
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(219 citation statements)
references
References 28 publications
7
209
0
3
Order By: Relevance
“…From current data it is unclear how best to store fecal samples in the long term. Frantzen et al [30] found that DNA fragments of >300 bp could not be ampli®ed by PCR in feces of baboons, suggesting that the success of PCR ampli®cation depended on the size of the PCR product. Sidhu et al [17] isolated bacterial DNA directly from fresh fecal samples for PCR or from the fecal culture inoculated into an anaerobic vial within 3±4 h of collection.…”
Section: Discussionmentioning
confidence: 99%
“…From current data it is unclear how best to store fecal samples in the long term. Frantzen et al [30] found that DNA fragments of >300 bp could not be ampli®ed by PCR in feces of baboons, suggesting that the success of PCR ampli®cation depended on the size of the PCR product. Sidhu et al [17] isolated bacterial DNA directly from fresh fecal samples for PCR or from the fecal culture inoculated into an anaerobic vial within 3±4 h of collection.…”
Section: Discussionmentioning
confidence: 99%
“…For example, field conditions (Murphy et al 2007), preservation methods (Frantzen et al 1998), and animal diet (e.g. PCR inhibitors in plants (Huber et al 2002)) may also influence amplification success.…”
Section: Discussionmentioning
confidence: 99%
“…Although the study conducted by Palomares et al (2002) also reported no significant differences in the successful amplification of samples of different ages, the results concerning the number of attempts to achieve successful amplification indicate the need to include the issue of age of the samples collected in the design of future studies aimed at identifying specific animals through fecal DNA. The intense discussion in the literature (e.g., Wasser et al, 1997;Frantzen et al, 1998;Roeder et al, 2004;SotoCalderon et al, 2009;Beja-Pereira et al, 2009), regarding suitable methods of fecal DNA preservation following collection in the field, shows that the natural degradation of DNA contained in the feces over time following defecation has a high impact on the success of the PCR process.…”
Section: Discussionmentioning
confidence: 99%